Diversity of Dinoflagellate Symbionts in Scyphozoan Hosts From Shallow Environments: The Mediterranean Sea and Cabo Frio (Rio de Janeiro, Brazil) - Dall’Olio, Lucija Raspor; Beran, Alfred; Flander-Putrle, Vesna; Malej, Alenka; Ramšak, Andreja (Frontiers in Marine Science, 2022)
Symbiotic scyphozoan jellyfish are poorly understood in terms of their symbionts and traits, as well as the ecological significance of this association. Dinoflagellate symbionts of the medusae Cotylorhiza tuberculata, Phyllorhiza punctata, and Cassiopea xamachana collected in the Mediterranean Sea and Cabo Frio (Rio de Janeiro, Brazil) were phylogenetically identified based on 28S rDNA and ITS2 haplotypes. The studied medusae harbour only one phylotype of symbionts in a time, but scyphozoan jellyfishes can associate with several types of symbionts. This study confirmed that the main symbionts of investigated scyphozoans belong to the genera Symbiodinium, Philozoon, and Breviolum. The associations between dinoflagellate symbionts and Cotylorhiza tuberculata changed from year to year, hosting Philozoon one year and Breviolum another. Invasive species in the Mediterranean Sea Phyllorhiza punctata harboured dinoflagellate symbionts of genus Symbiodinium as in the native areal. Pigment analysis of two shallow-water symbiont species Breviolum sp. and Philozoon medusarum revealed characteristic profiles for each genus.